Fatores associados à adesão à terapia antirretroviral em pessoas em situação de rua: revisão integrativa - Teixeira, Lorena da Silva (Brasil, 2024)
Antiretroviral therapy (ART) has transformed AIDS into a controllable disease and, in the national context, public policies have contributed to universal access to ART, resulting in a reduction in AIDS-related mortality. However, adherence to ART remains a challenge, especially for homeless people, who face several socioeconomic and psychosocial barriers. These difficulties reflect the deep Brazilian social inequality, highlighting the need for more effective policies to guarantee access to treatment for this vulnerable population. Thus, the present study sought to identify in the scientific literature the factors that influence adherence to antiretroviral treatment in people living on the streets, based on consultation in the Lilacs, Medline, SciELO and Web of Science databases of articles published between 2017 and 2023. The review included 5 articles that pointed out multiple factors related to adherence to ART in homeless people, such as concern about other priorities besides health, not having an adequate place to store medications, abuse of alcohol and other drugs, the low level of formal education, prejudice and discrimination, difficulty in accessing health services, difficult access to food and the emotionally complex experience related to living on the street. The factors found were described and analyzed in the following categories: individual factors, social factors, economic factors and psychological factors. Multidisciplinary action is extremely important to ensure adequate support for people living with HIV/AIDS (PLWHA) living on the streets in care strategies, as well as the inclusion of the community in these strategies to combat the stigma associated with PLWHA and promote awareness about the importance of adherence to antiretroviral therapy (ART) to guarantee a better quality of life.